“Ó vós que entrais perdei toda a esperança”. The aesthetics of resistance in Argentinian cinema - Graziadei, Neiva Maria Mallmann (2019)
This article aims at approaching the concept of resistance as it is portrayed in five movies produced throughout the civil-military dictatorship in Argentina and which took place in the 1970s and 1980s. Despite its ending, this period still causes, in the intellectual and in other Argentinian sectors in general, aesthetic reactions which are contrary to the one followed by the regime. My hypothesis is that the movies, La historia oficial (1985), La noche de los lápices (1986), Garage Olimpo (1999), Kamchatka (2002) and Kóblic (2016) which will be analysed throughout the text, result from an open and very present memory in the Argentinian movie industry, in a clear attitude of resistance not only to the dictatorship itself but also to the attempts to erase memories.